Administration of rabies immunoglobulin: Improving evidence‐based guidance for wound infiltration. Issue 8 (5th July 2021) - Bookstaver, P. Brandon; Akpunonu, Peter; Nguyen, Huy‐Binh; Swan, Joshua T.; Howington, Gavin T.
Abstract: Rabies virus causes a fatal infection of the brain and spinal cord, accounting for approximately 59, 000 deaths globally each year. Rabies postexposure prophylaxis (PEP), including both rabies immunoglobulin (RIG) and vaccination, is administered to 55, 000 patients annually in the United States. With a nearly 100% case fatality rate, the optimal administration of rabies PEP cannot be understated. Updated rabies PEP guidelines issued by the World Health Organization (WHO) in 2018 recognized that local wound infiltration of RIG is the primary mechanism of protection, and the WHO now recommends only infiltration of wounds without distal intramuscular injection. We highlight potential points of failure involving wound infiltration of RIG, small‐volume doses, and large‐volume doses that may lead to suboptimal care and discuss implications of recent shifts toward evidence‐based guidelines using wound type and RIG volumes.